Sb distribution in the phases of SiO2 saturated Sb-Fe-O-SiO2-CaO system in air - Zhang Z.T.; Nie H.P.; Yan K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Sb distribution in the phases of SiO2 saturated Sb-Fe-O-SiO2-CaO system was determined for the first time through hightemperature experiment and quenching techniques, followed by Electron probe X-ray microanalysis (EPMA) in air (Ptot = 1 atm, PO2 = 0.21 atm). The phases were quantified in the temperature range of 900°C-1200°C and the effects of Fe/SiO2 (mass fraction) and CaO/SiO2 (mass fraction) on Sb2O3 content in the Sb-Fe-O-SiO2-CaO system were investigated at 1200°C. The results indicated that the Sb-containing phase primarily existed in the solid solution phase at 1200°C. With the increase of temperature from 1100°C to 1200°C, the Sb2O3 content in the solid solution phase increased drastically from 7.52 wt% to 17.36 wt%. Lowering the values of CaO/SiO2 and Fe/SiO2 in the smelting process effectively reduced Sb2O3 content in the slag. The verification of the experiment results suggested that the antimony content in slag was 0.57 wt%, the crude antimony yield rate was lower than 4%, and the crude antimony grade was beyond 94 wt%, which meant that the reduction of antimony content in the slag could be achieved.